2011
DOI: 10.2741/3730
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoids as potential agents for the chemoprevention and therapy of breast cancer

Abstract: Breast cancer remains a major cause of death in the United States as well as the rest of the world. In view of the limited treatment options for patients with advanced breast cancer, preventive and novel therapeutic approaches play an important role in combating this disease. The plant-derived triterpenoids, commonly used for medicinal purposes in many Asian countries, posses various pharmacological properties. A large number of triterpenoids are known to exhibit cytotoxicity against a variety of tumor cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 287 publications
(203 citation statements)
references
References 97 publications
6
180
0
Order By: Relevance
“…A large number of tri-terpenoids have been shown to suppress the growth of a variety of cancer cells without exerting any toxicity in normal cells [57][58][59] . Numerous preclinical efficacy studies have provided extensive evidence that both naturally occurring and synthetic derivatives of triterpenoids possess chemopreventive and therapeutic effects against colon, breast, prostate and skin cancer [56,[60][61][62][63][64] . These triterpenoids and their derivatives act at various stages of tumor development, inhibit initiation and promotion of carcinogenesis, induce tumor cell differentiation and apoptosis, and suppress tumor angiogenesis, invasion and metastasis through regulation of various transcription and growth factors as well as intracellular signaling mechanisms [56,[64][65][66] .…”
Section: Terpenoidsmentioning
confidence: 99%
“…A large number of tri-terpenoids have been shown to suppress the growth of a variety of cancer cells without exerting any toxicity in normal cells [57][58][59] . Numerous preclinical efficacy studies have provided extensive evidence that both naturally occurring and synthetic derivatives of triterpenoids possess chemopreventive and therapeutic effects against colon, breast, prostate and skin cancer [56,[60][61][62][63][64] . These triterpenoids and their derivatives act at various stages of tumor development, inhibit initiation and promotion of carcinogenesis, induce tumor cell differentiation and apoptosis, and suppress tumor angiogenesis, invasion and metastasis through regulation of various transcription and growth factors as well as intracellular signaling mechanisms [56,[64][65][66] .…”
Section: Terpenoidsmentioning
confidence: 99%
“…Previous studies showed that the main active ingredients of A. cinnamomea are antroquinonol [5], succinic acid, maleic acid [6], benzenoids [7], triterpenoids [8], and polysaccharides [9]. Among these components, triterpenoid constitutes the largest group of phytochemicals in all living organisms [10]; as such, studies have mainly focused on this group. Most triterpenoids are isolated from plants and utilized as commercial flavorings and medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Amooranin, an oleanane pentacyclic triterpenoid isolated from the stem bark of Amoora rohituka has been shown to inhibit proliferation and induced apoptosis of MCF-7 and MDA-MB-468 cells via caspase activation pathway compared to normal breast epithelial cells MCF-10A. Additional studies using a synthetic derivative amooranin methyl ester showed potent activity against breast cancer cells at nanomolar range and inhibited Ehrlich ascites tumor in swiss mice [153]. Synthetic OA derivatives modulated multiple signaling pathways and intracellular signaling molecules including NF-jB, AKT, STAT3, mTOR, caspases-3, -8, and -9, ICAM-1, VEGF, and PARP in a variety of cancer cells [14,[154][155][156].…”
Section: Oleanolic Acidmentioning
confidence: 99%